Recognition and measurement of cryptocurrencies pursuant to IFRS - Tobias Holz (2022)
In recent years, the importance of the internet has drastically increased. We live in times of industry 4.0, artificial intelligence, global online markets, and access to worldwide content. In the course of these developments, a universal, digital currency was the next logical step in order for people to easily pay their invoices without having problematic encounters with exchange rates or fees for foreign purchases. Nowadays, we refer to this currency as cryptocurrency, with its best-known provider being Bitcoin. But the creation of this currency has raised questions in the field of accounting. How do accountants recognize this item and how do they measure it? These issues are not fully resolved as of today and may be subject to change in the future. Therefore, this paper aims to draw a picture about the components of cryptocurrency and its safety precautions and attempts to take it into the perspective of IFRS, thereby attempting to illustrate what this currency is and how accountants can deal with this innovation.
Keywords: Cryptocurrency; Bitcoin; Blockchain; IFRS; Fair Value